Immunomodulatory Effects of Vitamin D in Pregnancy and Beyond - Cyprian, Farhan; Lefkou, Eleftheria; Varoudi, Katerina; Girardi, Guillermina (Frontiers in Immunology, 2019)
In addition to its role in calcium homeostasis and bone formation, a modulatory role of the active form of vitamin D on cells of the immune system, particularly T lymphocytes, has been described. The effects of vitamin D on the production and action of several cytokines has been intensively investigated in recent years. In this connection, deficiency of vitamin D has been associated with several autoimmune diseases, including type I diabetes mellitus (T1DM), multiple sclerosis (MS), inflammatory bowel disease (IBD), systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA). In a successful pregnancy, the maternal immune response needs to adapt to accommodate the semiallogeneic fetus. Disturbances in maternal tolerance are implicated in infertility and pregnancy complications such as miscarriages (RM) and preeclampsia (PE). It is well known that a subset of T lymphocytes, regulatory T cells (Tregs) exhibit potent suppressive activity and have a crucial role in curtailing the destructive response of the immune system during pregnancy and preventing autoimmune diseases. Interestingly, vitamin D deficiency is common in pregnant women, despite the widespread use of prenatal vitamins, and adverse pregnancy outcomes such as RM, PE, and low birth weight have been linked to low vitamin D levels during pregnancy. Research has shown that autoimmune diseases have a significant prevalence within the female population, and women with autoimmune disorders are at higher risk for adverse pregnancy outcomes. Provocatively, dysregulation of T cells plays a crucial role in the pathogenesis of autoimmunity and adverse pregnancy outcomes where these pathologies are also associated with deficiency of vitamin D. This article reviews the immunomodulatory role of vitamin D in autoimmune diseases and pregnancy. In particular, we will describe the role of vitamin D from conception until delivery, including the offspring neurodevelopment. This review will also discuss an observational study in which vitamin D levels were measured in pregnant women with autoimmune disease antiphospholipid syndrome, frequently associated with adverse pregnancy outcomes.